Microtremor and Geolistrik Resistivity Study Around the Trans Timor Primary Arterial Road for Disaster Mitigation - Harti Umbu Mala; Adi Susilo; Sunaryo Sunaryo (Natural B, Journal of Health and Environmental Sciences, 2015)
The research on microtremor and geoelectric resistivity around Trans Timor Primary Artery Road to disaster mitigation, has been done. The aims of this research were to obtain the Peak Ground Acceleration (PGA) value, the soil dominant frequency, seismic vulnerability index and to estimate the thickness of sediment layer. Microtremor data collection was done by using a three-component seismometer, DS-4A feedback short-period, at 52 points with 250 m interval. Dominant frequency and amplification factors were obtained by using curve analysis method, horizontal to vertical spectral ratio (HVSR). The PGA value was calculated using Kanai empirical equations, where the data of dominant period were obtained from the inversion of frequency values while the parameters of the earthquake were based on seismic events in the last 50 years, from 1963 to 2013 with magnitude of ≥ 3. Geoelectric measurements were conducted using a Resistivity-meter OYO, based on Wenner Schlumberger configuration and it was divided into two lines, with length of 400 m each.  From the results obtained by PGA value is ranged between 80 and 500 gal with level of risk moderate two to very large one. The distribution value of the soil dominant frequency was 0.62 Hz-18.27 Hz, while the distribution of the seismic vulnerability index ranged from 0.21 to 21.83. The type of soil is dominated by clay and alluvium as top soil and its thickness varies from 10 m to 50 m, strengthened by limestone as bedrock.